High-Fat Diet Induces Periodontitis in Mice through Lipopolysaccharides (LPS) Receptor Signaling: Protective Action of Estrogens - Blasco-Baque, Vincent (Public Library of Science, 2012)
BACKGROUND: A fat-enriched diet favors the development of gram negative bacteria in the intestine which is linked to the occurrence of type 2 diabetes (T2D). Interestingly, some pathogenic gram negative bacteria are commonly associated with the development of periodontitis which, like T2D, is characterized by a chronic low-grade inflammation. Moreover, estrogens have been shown to regulate glucose homeostasis via an LPS receptor dependent immune-modulation. In this study, we evaluated whether diet-induced metabolic disease would favor the development of periodontitis in mice. In addition, the regulatory role of estrogens in this process was assessed. METHODS: Four-week-old C57BL6/J WT and CD14 (part of the TLR-4 machinery for LPS-recognition) knock-out female mice were ovariectomised and subcutaneously implanted with pellets releasing either placebo or 17β-estradiol (E2). Mice were then fed with either a normal chow or a high-fat diet for four weeks. The development of diabetes was monitored by an intraperitoneal glucose-tolerance test and plasma insulin concentration while periodontitis was assessed by identification of pathogens, quantification of periodontal soft tissue inflammation and alveolar bone loss. RESULTS: The fat-enriched diet increased the prevalence of periodontal pathogenic microbiota like Fusobacterium nucleatum and Prevotella intermedia, gingival inflammation and alveolar bone loss. E2 treatment prevented this effect and CD14 knock-out mice resisted high-fat diet-induced periodontal defects. CONCLUSIONS/SIGNIFICANCE: Our data show that mice fed with a diabetogenic diet developed defects and microflora of tooth supporting-tissues typically associated with periodontitis. Moreover, our results suggest a causal link between the activation of the LPS pathway on innate immunity by periodontal microbiota and HFD-induced periodontitis, a pathophysiological mechanism that could be targeted by estrogens.